Systematization of Nursing Care in Health Units: An integrative review (Research, Society and Development, 2021)
Objective: To analyze Brazilian articles on the Systematization of Nursing Assistance (SAE). Methodology: integrative review, with a narrative approach. Data collection was performed by searching the Scielo (Scientific Electronic Library Online) and Lilacs (Latin American and Caribbean Literature in Health Sciences) databases using the terms "Nursing", "Nursing Process", ”“ Health Centers ”,“ Nursing Team ”,“ Nursing Care ”,“ ILP ”and“ Primary Care ”, articles published until 2021. Results: Sixteen articles were listed and analyzed, which addressed the guiding question and criteria of inclusion. The study served to highlight the importance of SAE in Health Units, as well as highlighting the means of implementation used in the researched articles. Conclusion: This study showed in the articles published between 2004 and 2021, and in all of them difficulties and possible solutions for the application of SAE in Health Units were pointed out. Despite the obstacles that nurses face to implement SAE , their significant contributions must be taken into account, proposing a moment for reflection by nursing professionals, especially nurses. The Systematization of Nursing Assistance is a commitment and humanization of care, and the effort to implement it in basic units, ILPS and hospital units is of great value.